Post-percutaneous core needle biopsy sputum cytology: diagnostic value and factors for positive prediction in diagnosing malignancy - Sang Kyu Lee; Hee Kang; Min Jung Jung; Sekyoung Park; Ki Nam Lee (Kosin Medical Journal, 2023)
Background This study evaluated the diagnostic yield and positive predictive factors of post-percutaneous core needle biopsy (PCNB) sputum cytology in diagnosing malignancy. Methods This retrospective study included patients who underwent PCNB at a single center from January 2014 to March 2022. Patient demographics, lung lesion characteristics on computed tomography, underlying lung disease, post-PCNB complications, histopathologic results of PCNB, post-PCNB sputum specimens, and final diagnoses were reviewed. The diagnostic yields and related factors were analyzed. Results Overall, 177 consecutive patients with sputum specimens obtained after PCNB for intrapulmonary lesions were enrolled. Among them, 152 patients had a final diagnosis of malignancy. Diagnostic sputum specimens with atypical or malignant cells were obtained in 12 patients. The sensitivity, specificity, accuracy, positive predictive value, and negative predictive value of sputum cytology were 7.89%, 100%, 20.90%, 100%, and 15.15%, respectively. Lesion size, air-bronchogram, lesion multiplicity, and the cell type of squamous cell and adenocarcinoma differed significantly between the groups with diagnostic versus non-diagnostic sputum (p<0.05). The lesion size (odds ratio [OR], 1.035; 95% confidence interval [CI], 1.008–1.064; p=0.013), presence of air-bronchogram (OR, 23.485; 95% CI, 2.532–217.316; p=0.005), and squamous cell carcinoma (OR, 7.397; 95% CI, 1.773–30.865; p=0.006) were significantly associated with a diagnostic sputum specimen post-PCNB. Conclusions Although post-PCNB sputum cytology had low sensitivity in diagnosing lung cancer, it showed diagnostic results in some peripheral lung cancer patients who have squamous cell types, relatively large tumors, and air-bronchograms in the lesions.